Dampak Pemanfaatan Iklan Pada Aplikasi Online - Cut Devi Maulidasari; Damrus Damrus; Tamitha Intassar Husen (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2022)
AbstractThe rapid development of internet technology makes online media very feasible to be used as a means to spread various types of advertisements for products that people need. Online advertising can be found on social media such as Instagram, Twitter, Youtube, Websites, and others that are accessed using the internet. It is interesting to see how useful the impact of advertising in online media is. The theory used in this study is the advertising theory of Kotler and Keller, while the method used in this study is a qualitative research method. The results of this study indicate the impact of the usefulness of advertising in online media including; The cost is relatively cheap, can reach a wide market, estimate the time required, introduce products and companies to the wider community, and so on. Based on these results, of course, advertising promotion in online media has a fairly effective and beneficial impact on the promotion of a company's products.Keywords: Advertising, Online Media, Impact of Advertising, Benefits of Online Advertising